Dadeni - Jones, Ifan Morgan (Y Lolfa, 2017)
An exciting fantasy novel which moves from rural Wales to the turmoil of the Assembly in Cardiff and to the Tower of London, peppered with a generous dollop of Welsh history and culture.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books